ALIH KODE DAN CAMPUR KODE PADA FILM ROMEO & JULIET KARYA ANDIBACHTIAR YUSUF - Nasrul Bagus Fajriansyah; Dede Sopianda; Cucu Kartini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The purpose of this article is to analyze the language that used in Romeo and Juliet movie by Andibachtiar Yusuf with switching code and mixing code. Analyzing the form of switching code and mixing code on the dialogue of Romeo and Juliet movie by Andibachtiar Yusuf. Language is a tool of communication or a tool of interaction that only human can have, therefore its defined as communication between humans, characterized by the use of spoken or random symbols (arbitrary) in the sense that has been received. The method of this research is descriptive qualitative method. It means that this research analyzing the data and the result of the data is present in the descriptive. From the analysis, there are five language that used in Romeo and Juliet movie, includes English, Indonesian, Sundanese, Javanese and Betawi. Moreover, the researcher could find phrases that are switching code and mixing code. There are five switching code and eighteen mixing code.